Reality Squared : Televisual Discourse on the Real - Friedman, James, 1958- (Book collections on Project MUSE., 2002)
Reality-based television has come to play a major role in both production decisions and network strategy. This text examines the representation of reality within the televisual viewing frame, as well as the exponential growth of these programmes.